The Effect of Singing with Audiovisual Media on Improving Toothbrushing Knowledge among Children: A Pre-Experimental Study - Santoso, Ibriani Nathania Margaretha; Akwan, Yulie Emilda; Wardani, Istien (Universitas Muhammadiyah Yogyakarta, 2026)
Dental health problems remain prevalent among elementary school children, yet conventional oral health education methods often fail to maintain engagement. Although singing and audiovisual media are known to enhance motivation and memory, evidence on their combined effectiveness for improving children’s toothbrushing knowledge, particularly in Indonesia, remains limited. To evaluate the effect of a singing-based audiovisual education intervention on the toothbrushing knowledge of 8–9-year-old children. A pre-experimental, pretest–posttest, one-group design was conducted with 40 third-grade students at SD Hang Tuah 6 Surabaya. The intervention consisted of a researcher-composed educational song accompanied by an audiovisual demonstration. Knowledge was assessed using a validated questionnaire, and differences between pre- and post-test scores were analyzed using the Wilcoxon signed-rank test. Before the intervention, 65% of students demonstrated good knowledge, and 35% demonstrated poor knowledge. After the intervention, all participants (100%) achieved good knowledge. The mean knowledge score increased significantly from 8.35 ± 1.12 to 9.85 ± 0.36 (p < 0.001), confirming the positive effect of the singing-based audiovisual approach. The Wilcoxon test revealed a statistically significant difference in knowledge levels before and after the intervention (Z = –4.872, p < 0.001), indicating a positive impact of the method on students’ learning outcomes. The singing-based audiovisual intervention effectively enhanced children's knowledge of proper toothbrushing techniques and may serve as an engaging, practical strategy for school-based oral health promotion programs.